Tinjauan Fiqih Muamalah Terhadap Akad Jual Beli Layanan Go-Food Pada Aplikasi Go-Jek - Nur Fitria Habiba; Najri Aulia; M.Rifqi Al Husaini; Junita Lubis; Lusi Febriani; Anju Syahrin Marpaung (Yayasan Dar Arrisyah Indonesia, 2025)
Currently, buying and selling transactions in Islam are growing rapidly, this is due to the development of the times and technology that has developed so much from time to time until now. From this development comes some of our study material, namely about transactions that are developing, one of which is some services in online applications, among others, Go-food in the Go-jek application. In this problem, of course, it raises challenges for Muslims to examine these developing transactions, whether they are in accordance with Sharia or otherwise. And in the above problems, the researcher raises the title that has been described above to become material for study in order to find out several types of contracts contained in the service application in the online application. In this study, researchers used a qualitative approach in the form of normative juridical, the method used was concept analysis. Research is carried out by looking for reference sources that are relevant to the study of the title to be researched above, reverence materials to be researched, such as from the latest journals, books, magazines, and other reference materials. So it can be concluded that the results of this study, it is found that in the lease agreement occurs between the service provider company, namely go-jek with service providers or ojek drivers. From the problem of this agreement whether it is in accordance with Islamic law or has not fulfilled Islamic law, and this is where the researcher is to study further about some of the contracts that have occurred in this problem. And this research can also help readers about the kinds of transaction contracts that have developed over time, and hopefully it can add insight to the readers about the discussion above.